A Two Year Follow-up Study on the Success Rate of Dr. Poons Metabolic Diet Program - Poon, Pat (Archives of Clinical and Biomedical Research, 2018)
Lifestyle management is the treatment of choice to combat obesity and its related complications. Diet counseling is the main stage of lifestyle management. Exercise, stress management, sleeping hygiene, emotional eating and food addiction counseling are needed in addition to a good diet program to ensure that the diet is maintainable. The diet that was prescribed to the patients should be inexpensive, fulfill the nutritional need, and maintainable. A study was designed to determine the effectiveness of Dr. Poon’s Metabolic Diet Program on weight reduction and weight maintenance. The result shows that when patients continue to attend the diet program, they were able to lose 10% of their initial weight on an average of 11 weeks and able to maintain the weight loss after two years. The average weight reduction after 2 years was 13.5%.